Empowering Primary School Teachers through Service-Learning-Based Classroom Action Research Training for Continous Improvement - Isnaini Wulandari Jumadi; Arrofa Acesta; Ndaru Mukti Oktaviani; Heri Herwanto; Eva Arnaz (IMPACTS: International Journal of Empowerment and Community Services, 2026)
Purpose This community service program aims to empower primary education teachers in conducting classroom action research as a strategy for continuous improvement, addressing their low research competence and limited understanding of classroom action research practices. Methods - The methodology for this community service is service learning. The activities include offering service activities to students, students registering for service activities, focus group discussions explaining the purpose of service activities to students, investigating problems, observing partners, and preparation for action, service action, and reflection. It was conducted in three meetings with 15 teachers at SDN 1 Mandirancan. Activities included workshops, focus group discussions, and mentoring. Data were collected through pre-test and post-test and analyzed using a paired sample t-test Purpose This community service program aims to empower primary education teachers in conducting classroom action research as a strategy for continuous improvement, addressing their low research competence and limited understanding of classroom action research practices. Methods - This study employed a service-learning approach involving university students as facilitators to support primary school teachers through workshops, focus group discussions, and mentoring sessions. It was conducted in three meetings with 15 teachers at SDN 1 Mandirancan. Activities included workshops, focus group discussions, and mentoring. Data were collected through pre-test and post-test and analyzed using a paired sample t-test Result and discussions - The findings indicate a significant improvement in teachers’ understanding and skills. The mean score increased from 62.40 (pre-test) to 81.73 (post-test), with t-value (5.87) > t-table (2.145), indicating statistical significance. Additionally, 73.33% of teachers were able to identify classroom problems and develop initial classroom action research proposals, while 80% showed increased confidence in data analysis. The service-learning approach effectively facilitated experiential learning, bridging theory and practice. Conclusion - The community service successfully enhanced teachers’ knowledge, skills, and confidence in conducting classroom action research. The integration of training and mentoring proved effective in supporting sustainable professional development and improving teaching practices.